SECURITY OF TENURE AT THE CROSSROAD OF CONFLICTING INTERESTS: THE BRUSSON FINANCE (PTY) LTD SAGA - CJ Tchawouo Mbiada (Obiter, 2014)
Section 26 of the South African Constitution of 1996 makes provision for the right to have access to adequate housing (right to housing) for everyone. The section further enjoins the State to devise measures within the availability of its resources, to progressively realise this right. This has led to the adoption/enactment and implementation of a number of statutes and policies such as the Housing Act (107 of 1997), the Breaking New Ground of 2004, the Upgrading of Informal Settlement Programme of 2004, the National Housing Programme for Housing Assistance in Emergency Housing Circumstances of 2004, the National Housing Code of 2009 and the Outcome 8 Delivery Agreements: Sustainable Human Settlements and Improved Quality of Household Life of 2010. In passing, adopting and implementing these statutes and policies, the Government is discharging its obligations under section 26 of the Constitution to provide housing to all citizens. However, the effort of the state to fulfil its constitutional mandate to realize the right to housing is under severe threat following the Brusson Finance (Pty) Ltd matter which I refer to as “saga” (hereinafter “Brusson”). The Brusson saga refers to a number of people who were fraudulently deprived of their property (used a guarantee) as a result of a well-orchestrated scam offering credit facilities to those with bad credit records who could no longer receive credit facilities from financial institutions. As a result of such fraudulent deprivation of their property, two of the victims launched proceedings to recover their property. That case and the subsequent one analysed below, are used only to illustrate the Brusson mechanism and difficulties encountered by victims to get back their property. Furthermore, there are other decided cases. Some other cases are likely to be lodged, all in connection with Brusson, hence the word “saga”. These cases serve only as a point of departure for this note, and comments made thereto go beyond the scope of the judgments. These comments are extended to the Brusson scheme in general and should not in any way, be constrained or limited to the findings of the court. In other words, the comments are not against the findings of the courts. The Brusson saga resuscitates the debate of the horizontal application of the Bill of Rights to private disputes when a violation of a constitutional right may be invoked by either party. This necessitates the granting of remedies other than those provided for by the relevant statutes when such remedies would not suffice to satisfactory remedies to all the parties. Unless such remedies are granted to salvage the situation, many beneficiaries from the Brusson scam will be left homeless (if not already) in the near future, thereby curtailing Government effort to provide security of tenure and reduce homelessness countrywide. In order to understand the difficulties and complexities encountered by all parties (court, liquidators and the National Credit Regulator) to transfer properties back to the original home owners, I provide an in-depth mechanism of the Brusson’s scheme.